PERAN MAKSUD DIDALAM DISONANSI KOGNITIF PESERTA PELATIHAN VOKASIONAL RENCANA USAHA DAN MANAJEMEN KEUANGAN KSM BINAAN BDC SRIWIJAYA PALEMBANG - Thoyib, Ellys; Harahap, Lily Rahmawati; Effendi, R.Y. (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
This study aims to determine the role of intention in cognitive dissonance among 70 participants in vocational training on business plan and financial management of micro small entrepreneurs in independent community groups (KSM) producers of pempek, kemplang kerupuk, jumputan, tajung, blongket and songket. The hope is to change the mindset of participants in traditional financial management into accountable financial management. This knowledge is a stimulus that will stimulate the intention, to be a strong predictor of forming attitudes and expected behavior. It turns out that after 4 months of training, only 5% of the participants implemented this material, while 95% did not. The results of the study of the authors obtained data that the positive intention in the cognitive system of participants is very high, ranging from 74% to 97%. There has been a cognitive dissonance in the participants' attitudes and behavior.So it can be concluded that positive intentions can be in line with attitudes and behaviors but may not, this can happen because there is no strong role from external elements, such as limited market prospects and channeling around them, capital and financial management have not been effective, quality of management and HR is not yet committed, the role of BDC as a coach is not optimal, it should be able to play an active role as the foster father of KSM.